Stock Allocation in Turkish Capital Markets: Industry and Firm Level Perspectives (European Journal of Marketing and Economics, 2024)
Investors' trading patterns have been an intensively researched topic in emerging markets due to their significant role and power in capital markets, and this paper explores the global and domestic factors driving the stock allocation of both domestic and foreign investors in Turkey between 2006 and 2016. Utilizing year-end data obtained from the Central Securities Depository Institution of Turkey, the study analyzes how major economic crises altered investors' attitudes toward equity allocation across different sectors, including the BIST Industrials, Financials, and Services indices. Furthermore, the paper provides a detailed classification of investors, breaking down individual and institutional categories into granular firm and industry levels, with specific focuses on mutual funds, corporate entities, and investment trusts. The research also provides critical insights into firm-level stock allocations by considering the behavior of responsible stockholders, demonstrating how corporate governance practices have been systematically strengthened by the growing influence of institutional investors within the financial system. Ultimately, these findings reveal the evolving investor profile of the BIST Corporate Governance Index during this highly volatile decade, offering valuable implications for policymakers and asset managers seeking to understand capital flight and institutional stabilization within emerging market ecosystems.
Keywords: stock allocation, institutional investors, industrial classification, corporate governance, responsible stockholder, Turkey